PENGEMBANGAN KURIKULUM PENDIDIKAN AGAMA ISLAM DALAM PENDEKATAN HUMANISTIK DI INDONESIA - Febri Widiandari; Tasman Hamami (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2022)
The curriculum is one of the main components in education. The curriculum is a compass for the direction where students want to be taken. As a tool to achieve dynamic educational goals, the curriculum must always be developed and refined to suit the times, so as to facilitate educational programs in the context of realizing and achieving national education goals. The curriculum has many approaches, one of which is a humanistic approach. This study aims to examine how the Islamic Religious Education curriculum in a humanistic approach. This research is based on literature study by taking data from library sources such as research journals, books, documents and others. The results of this study indicate that the Islamic Religious Education curriculum with a humanistic approach is suitable for use in Indonesia in an effort to develop the potential of students. Humanistic education begins with the idea of ​​"humanizing humans". This means that every human being brings their respective potentials in order to develop their lives with the potential they have.